Integrating Community Outreach into Next Generation Science Standards for Prospective Science Teachers' Sustainable Climate Action Skills - Parmin; Jabbar, Abdul; Rahayu, Endah Fitriani; Pamelasari, Stephani Diah; Sukmawati, Ika; Alamsyah, Muhammad Radian Nur (Jurnal Pendidikan IPA Indonesia, 2025)
Human behavior that impacts climate change is increasingly out of control, which is very worrying for the survival of future generations. The weak climate-action skills of prospective science teachers, along with their daily activities that have the potential to cause climate change, need to be addressed. This study aims to integrate community outreach into the three dimensions of the Next Generation Science Standards so that prospective science teachers are skilled at preventing climate change. This study uses a mixed-methods embedded experimental design with a quasi-experimental component. Community outreach is integrated into the three dimensions of NGSS to develop the climate action skills of prospective science teachers by learning from community habits for climate change prevention practices. The study results showed that prospective science teachers are increasingly skilled at preventing climate change by planting trees and sorting organic and inorganic waste, thereby demonstrating economic potential. Integrating community outreach into the three dimensions of NGSS is a new strategy to prepare prospective teachers who are aware of being agents of sustainable climate change prevention.